From the mental patient to the person - Barham, Peter; Hayward, Robert (Travistock/Routledge, 1991)
Contributes to the debate on contemporary health policy aimed at closing mental hospitals through an exploration of the experiences of a group of people with a history of schizophrenic illness, who are living in the community.